PROSPECTS DOMESTIC DRUGS DIBIKOR (TAURINE) IN PATIENTS WITH MYOCARDIAL INFARCTION, AND STABLE ANGINA - V. V. Rezvan; I. S. Vasilyeva; N. V. Strizhova; D. L. Vinogradov (SINAPS LLC, 2016)
It was performed the evaluation of the clinical efficacy of taurine in the treatment of postinfarction cardiosclerosis (PIC). 57 patients (mean age 60,2 ± 14,3 years) with evidence of PIC and angina. When incorporated into standard therapy taurine showed a statistically significant improvement (compared to placebo) subjective performance status patients, normalize echocardiographic indices (increase of the ejection fraction) and laboratory parameters (reducing the concentration of total cholesterol, triglycerides, low density lipoprotein). The changes revealed clinical and instrumental parameters are stored for 3 months after receiving taurine. It is recommended to add taurine in a daily dose of 750 mg to standard therapy in patients with postinfarction cardiosclerosis with a view to its potentiating effect by improving the metabolic processes in the myocardium.